Steels processing, structure, and performance - Krauss, George, 1933- (ASM International, 2005)
Steels: Processing, Structure, and Performance is a comprehensive guide to the broad, dynamic physical metallurgy of steels. The volume is an extensively revised and updated edition of the classic 1990 book Steels: Heat Treatment and Processing Principles. Eleven new chapters expand the coverage in the previous edition, and other chapters have been reorganized and updated. This volume is an essential reference for anyone who makes, uses, studies, or designs with steel. The interrelationships between chemistry, processing, structure, and performance--the elements of physical metallurgy--are integrated for all the types of steel discussed. The evolution, characterization, and performance of steel microstructures are described, with increased emphasis on deformation and fracture. Heat treatment remains a vital aspect of the manufacture of steel products, and the coverage of thermal processing and its effect on steels is expanded in this edition.-Dramatic changes in steel manufacture have occurred in the 15 years since the publication of the 1990 edition. Low-carbon sheet steels have experienced the most dynamic changes: thermal processing of sheet steels on a massive continuous scale has produced new grades with only subtle changes in chemistry. Low carbon sheet steels, together with strengthening mechanisms, developments in microalloyed forging steels, steels with bainitic and a variety of ferritic microstructures, quench and tempered steel performance, high-carbon steels for rail and ultra-high strength wire, and the causes of low toughness and embrittlement are all discussed in new chapters. Brief coverage is provided on the history of steel, including the time frame for important developments. A link to steelmaking and solidification is made in the chapter on the effects of primary processing on steel microstructure. The text is meant to be informative, readable, up-to-date, and self contained.-Principles, concepts, and understanding of microstructural evolution and performance, within the framework of processing and properties, are illustrated, by plots of data, micrographs and schematic diagrams. A special effort has been made to include references to the most pertinent books, reviews, and technical papers on a given subject. About the Author Dr. George Krauss is currently University Emeritus Professor at the Colorado School of Mines and a metallurgical consultant specializing in steel microstructural systems. He served at Lehigh University as Assistant Professor, Associate Professor, and Professor of Metallurgy and Materials Science from 1963 to 1975, and in 1975, joined the faculty of the Colorado School of Mines as the AMAX Foundation Professor in Physical Metallurgy. He was the John Henry Moore Professor of Metallurgical and Materials Engineering at the time of his retirement from the Colorado School of Mines in 1997. In 1984, Dr.-Krauss was a principal in the establishment of the Advanced Steel Processing and Products Research Center, a National Science Foundation Industry-University cooperative research center at the Colorado School of Mines, and served as its first Director until 1993. In addition to the three editions of the present volume, he coauthored the book Tool Steels, Fifth Edition, ASM International, 1998, and edited or co-edited conference volumes on tempering of steel, carburizing, zinc-based coatings on steel, and microalloyed forging steels. He has published over 300 papers and lectured widely in technical conferences, universities, corporations and ASM International chapters, including a number of keynote, invited and honorary lectures. He presented the Edward DeMille Campbell Memorial Lecture of ASM International in 2000 and the Howe Memorial Lecture of the Iron and Steel Society in 2003. Dr.-Krauss has served as the President of the International Federation of Heat Treatment and Surface Engineering (IFHTSE), 1989-91, and as President of ASM International, 1996-97. He is Fellow of ASM International, TMS, and IFHTSE. He has been awarded the Adolf Martens Medal of the German Society for Heat Treatment and Materials, the Charles S. Barrett Silver Medal of the Rocky Mountain Chapter of ASM, the George Brown Gold Medal of 3.
Keywords: Steel.; elektronické knihy; electronic books